On almost quasi-hyperideals in semihypergroups. (2nd January 2021) - Suebsung, Sudaporn; Yonthanthum, Winita; Hila, Kostaq; Chinram, Ronnason
Abstract: In this paper, we define almost quasi-hyperideals in semihypergroups and give some interesting properties.